Acute Dynamic Exercise Increases Fibrinolytic Activity - Rankinen, Tuomo; Väisänen, Sari; Penttilä, llkka; Rauramaa, Rainer (Thrombosis and Haemostasis, 1995)
The influence of acute bouts of dynamic exercise on plasma tissue plasminogen activator (tPA), plasminogen activator inhibitor (PAI) and fibrinogen was investigated on nine healthy non-smoking men aged 23 to 37 years. Subjects performed maximal and two submaximal (duration 30 min, intensity 50% [aerobic threshold] and 78% [anaerobic threshold] V02max) bicycle ergospirometry tests separated by seven days. The order of the submaximal tests was randomized. Blood samples were drawn before, immediately after and 24 h after each test. Plasma tPA and PAI activities were measured amidolytically, and fibrinogen concentration by thrombin method. All postexercise values were corrected for the change in plasma volume. The pre-exercise tPA and PAI activities and fibrinogen concentration were similar in each tests. tPA activity increased during each test (from 2.0 [SEM 0.24] IU/ml to 20.3 [3.14] during maximal, 2.0 [0.22] to 19.0 [2.59] during anaerobic threshold test, 1.8 [0.22] to 5.5 [0.82] during aerobic threshold; p <0.001 during all tests, p = 0.01 aerobic threshold vs maximal and anaerobic threshold). PAI activity decreased during maximal (from 6.6 [2.51] AU/ml to 2.0 [2.00], p <0.05) and anaerobic threshold (5.0 [2.07] to 0.2 [0.22], p <0.01) tests but not during aerobic threshold test (7.0 [3.69] to 4.5 [2.93], p = 0.123). One subject had clearly higher pre-exercise PAI activity and smaller tPA response to exercise as compared to other subjects. All 24 h post-exercise activities were similar to pre-exercise values. Plasma fibrinogen concentration did not change during any tests. Single acute bouts of dynamic exercise transiently increase tPA and decrease PAI activity without affecting plasma fibrinogen concentration in healthy young men.